Mechanically separated meat prepared with edible tilapia filleting waste from a public fish market - Bacelar, Rafael Gomes Abreu; Moura, Nathálya de Oliveira; Sousa, Marília da Silva; Santos Filho, José Humberto; Rodrigues, Karina dos Santos; Melo, Eveny Silva de; Muratori, Maria Christina Sanches (Acta Scientiarum. Animal Sciences, 2023)
This study aimed to produce mechanically separated meat (MSM) from tilapia obtained at the Teresina fish market in the state of Piauí, Brazil. Waste production and disposal and yields were estimated, and physico-chemical and microbiological MSM qualities were determined. A questionnaire was applied to the fish market sellers, followed by tilapia carcass sampling for MSM production and assessments concerning yields, microbiological (Escherichia coli and Staphylococcus coagulase positive counts and the detection of Salmonella spp.) and physicochemical (water activity, pH, reaction to hydrogen sulfide and ammonia) quality and proximate composition (moisture, ash, proteins, lipids, carbohydrates and total energy value). The questionnaire results indicated that tilapia is highly in demand and thats processing leads to significant waste. The yield analysis indicated that tilapia MSM presents adequate residual meat extraction rates from tilapia carcasses. All microbiological analyses were in compliance with Brazilian standards. Physicochemical results were as follows: protein (14.9 to 16.1%), lipids (16.6 to 22.1%), ash (1.3 to 2.8%), moisture (60.6 to 64 .1%), carbohydrates (0.6 to 1.5%) and calories (216.5 to 263.1 kcal 100-1). It is, therefore, clear that MSM constitutes a safe and nutritious foodstudd and comprises a viable alternative for the development of co-products.